White matter micro- and macrostructure brain charts for the human lifespan - Michael E. Kim; Chenyu Gao; Karthik Ramadass; Nancy R. Newlin; Praitayini Kanakaraj; Sam Bogdanov; Gaurav Rudravaram; Derek Archer; Timothy J. Hohman; Angela L. Jefferson; Victoria L. Morgan; Alexandra Roche; et al. (Nature, 2026)
Abstract The human brain relies on a complex network of connections to function, with white matter acting as the primary communication highway between different brain regions 1,2 . Disruptions in these critical communication pathways are linked to several neurological, psychiatric and developmental disorders 3,4 . Although clinicians have long used standard growth charts to track physical development 5 , with more recent work translating these to whole-brain and grey matter measurements 6–9 , there has been no equivalent reference standard for white matter. Establishing a readily available normative reference is an imperative first step if we hope to utilize these white matter structural biomarkers clinically. Here we present lifespan reference charts for human brain white matter. By processing and standardizing 35,120 brain scans from diverse global studies, we mapped the typical growth, maturation and age-related decline of specific brain pathways from birth to 100 years of age. These reference charts establish a fundamental benchmark for healthy brain development and ageing, allowing researchers and clinicians to quantify how an individual’s brain deviates from typical patterns and highlighting disorder-related alterations. Furthermore, the accompanying open access charts enable the scientific and clinical communities to evaluate new patient and research data against these normative baselines, facilitating future clinical and neuroscience studies.